2007
DOI: 10.4070/kcj.2007.37.5.196
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Role of Serum Uric Acid for Predicting Cardiovascular Events in Patients with Coronary Artery Disease

Abstract: Background and Objectives:Serum uric acid has been reported to be an independent risk factor for coronary artery disease (CAD) and a predictor of mortality in patients with CAD. Yet there is gender difference for the serum uric acid levels. We evaluated the influence of the uric acid levels on major adverse cardiovascular events (MACEs) in patients with CAD according to their gender. Subjects and Methods:Of the 777 patients with angiographically proven CAD, 660 patients (378 males, 57.3%) were followed up a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…It has also been demonstrated that serum uric acid levels predicted cardiovascular events in male patients with CAD, and only the highest uric acid quartile was a predictor of cardiovascular events in women [32]. However, there was no relationship between uric acid and premature CAD within each gender group in the present study.…”
Section: Discussioncontrasting
confidence: 54%
“…It has also been demonstrated that serum uric acid levels predicted cardiovascular events in male patients with CAD, and only the highest uric acid quartile was a predictor of cardiovascular events in women [32]. However, there was no relationship between uric acid and premature CAD within each gender group in the present study.…”
Section: Discussioncontrasting
confidence: 54%
“…Of the 65 screened abstracts, 22 studies were retrieved for detailed evaluation. Of those 22, 2 studies were based on the same patient population, so they were considered as 1 study in the meta‐analysis (21, 22). One study was excluded because it reported insufficient data on stroke outcome (23).…”
Section: Methodsmentioning
confidence: 99%
“…They suggested that hypoxia was associated with a remarkable increase in hypoxanthine and inosine. Additionally, serum uric acid, the final product of purine metabolites, has been reported to be a predictor of mortality and morbidity in patients with MI [60], and is affected with sex differences [61,62]. However, no previous studies have investigated the influences of uric acid precursors on gender differences in MI.…”
Section: Discussionmentioning
confidence: 96%